ORGANIZATIONAL DEVELOPMENT AND CORPORATE OUTCOMES IN OWERRI-BASED HEALTH FACILITIES - NJOKU, Kenneth Chukwudi, PhD; UZODIMMA, Emmanuel Ezenwa, PhD (Journal of the Management Sciences, 2023)
The study investigated organizational development and corporate outcomes in Owerri-based health facilities. The objectives of the study were to examine the relationship between sensitivity training and capacity expansion; investigate the extent to which sensitivity training influenced employee retention; assess the relationship between team building and capacity expansion; and evaluate the extent to which team building influenced employee retention in health facilities in Owerri. Four research questions and four hypotheses guided the study. SWOT Analysis Model was used to beef up the study. The researchers employed the survey research design in the research. A structured questionnaire was the major instrument for data collection. Data analysis was committed to descriptive statistics of mean and standard deviation. Cronbach Alpha statistics was used for determining reliability ratio of the survey instrument. Correlation analysis was used to test hypotheses. It was found that each of sensitivity training and team building positively and significantly impacted on capacity expansion and employee retention in health facilities in Owerri. It was concluded that organizational development indices were drivers of corporate outcomes in Owerri-based health facilities. The study recommended that management of health facilities should always train workers on organizational development techniques. Sensitivity training should always be embraced by all workers for improved corporate outcomes; management should design other strategies for expanding capacity and corporate policies should be developed to enhance the use of team building in health facilities for overall corporate wellbeing and sustainability.